2022
DOI: 10.1186/s13031-021-00432-y
|View full text |Cite
|
Sign up to set email alerts
|

I don't leave my people; They need me: Qualitative research of local health care professionals' working motivations in Syria

Abstract: Background The Syrian conflict has endured for a decade, causing one of the most significant humanitarian crises since World War II. The conflict has inflicted massive damage to civil infrastructure, and not even the health care sector has been spared. On the contrary, health care has been targeted, and as a result, many health professionals have left the country. Despite the life-threatening condition, many health professionals continued to work inside Syria even in the middle of the acute cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…One participant emphatically expressed her religious inclinations towards patients and the community. Similar coping strategies were identified amongst HCWs in Yemen including fatalism [24] and in Syria participants had both intrinsic (humanitarian) and ideological (religious) reasons for staying at work [23]. Hospital administration has a vital role in ensuring job satisfaction amongst workers and according to our study the hospital administration did not fail in this aspect.…”
Section: Motivation To Worksupporting
confidence: 77%
See 1 more Smart Citation
“…One participant emphatically expressed her religious inclinations towards patients and the community. Similar coping strategies were identified amongst HCWs in Yemen including fatalism [24] and in Syria participants had both intrinsic (humanitarian) and ideological (religious) reasons for staying at work [23]. Hospital administration has a vital role in ensuring job satisfaction amongst workers and according to our study the hospital administration did not fail in this aspect.…”
Section: Motivation To Worksupporting
confidence: 77%
“…Behavioral studies have identified factors that promote job satisfaction such as conducive work environment, career progression or promotion, remuneration, adequate working conditions and recognition [22,23]. In conflict setting however, motivations may change such as is the case in our study, where participants' main motivation was their moral obligation to improve lives and reduce suffering and their ability to lead a relatively comfortable life.…”
Section: Motivation To Workmentioning
confidence: 74%
“…In the world stage, countries with insufficient health systems like Bangladesh are overburdened by pandemic breakouts when health services are desperately required [ 29 ]. Evidence suggests that during the first year of the COVID-19 pandemic, many healthcare workers experienced additional stress, psychological problems, lack of personal protective equipment (PPE), were excluded or stigmatized, lack of sufficient incentives, absence of coordination, and had management issues [ 29 , 30 ], which may have affected their attendance and behavior. Furthermore, studies showed that frontline healthcare workers in humanitarian contexts are particularly vulnerable to COVID-19 [ 31 ] which also added to the stigma and contributed to the absenteeism of healthcare workers during the initial COVID-19 lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…In Syria, COVID-19 research is relatively limited, especially related to the experiences and practices of ordinary Syrians that can play a significant role in mitigating transmission in areas with minimal governance or local authority support [20][21][22][23]. The COVID-19 pandemic has exacerbated ongoing socioeconomic challenges [14,24]. The first COVID-19 case was officially reported in Damascus in 22 March 2020 [14], followed by initial reported cases on 2 April 2020 in AACA [25] and 9 July 2020 in OCA [26].…”
Section: Plos Onementioning
confidence: 99%